Application of Low Temperature and Antiviral for Elimination of Chrysanthemum stunt viroid and Its Effect on the Growth of Shoot Tip Culture of Chrysanthemum - Diningsih, Erniawati; Aryantika, Safani; Rahardjo, Indijarto Budi; Nuryani, Wakiah; Hanudin; Manzila, Ifa (Jurnal Fitopatologi Indonesia, 2023)
Application of Low Temperature and Antiviral for Elimination of Chrysanthemum stunt viroid and Its Effect on the Growth of Shoot Tip Culture of Chrysanthemum Chrysanthemum stunt viroid has been widely reported to be a limiting factor in the production of chrysanthemum cut flowers. The aim of this study was to determine the effect of low temperature treatment (5 ℃) and antiviral ribavirin on the growth and elimination of Chrysanthemum stunt viroid (CSVd) in chrysanthemum plantlets cultured from shoot tips. CSVd infected plants were obtained from a government experimental garden in Cianjur, West Java. The research was carried out in several stages, namely 1) plant sampling, 2) viroid detection using RT-PCR method, 3) initiation of explants and propagation of plant material in vitro, 4) low temperature treatment 5 ℃ with three levels of incubation time at 1, 3, and 5 months, 5) ribavirin antiviral treatment with three levels of concentration (25, 100, and 125 ppm), and 6) confirmation of viroid-free plant materials by RT-PCR. The results showed that low temperature storage and ribavirin treatment reduced the rate of growth of shoot height and number of leaves. Ribavirin did not cause phytotoxity up to concentration level of 125 ppm, although it caused inhibition on shoot growth and leaf number. However, the combination of low temperature treatment (1, 3, and 5 months) with ribavirin (25, 100, and 125 ppm) was not able to eliminate CSVd from tissues at all treatment levels.